2019
DOI: 10.1038/s41598-019-39260-9
|View full text |Cite
|
Sign up to set email alerts
|

Analytical model of surface second-harmonic generation

Abstract: The process of second-harmonic generation (SHG) in a finite one-dimensional nonlinear medium is analyzed in parallel by the Green-function technique and the Fourier-transform method. Considering the fundamental pump field propagating along a given direction and eliminating back-reflections at the boundaries the terms giving the surface second-harmonic fields in the particular solution of the wave equation are uniquely identified. Using these terms the flow of energy corresponding to the surface second-harmonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…In this limitation, we suppose that the energy conversion to the second harmonic is very low such that the fundamental wave remains essentially undepleted. This process is known as a non-depletion approximation in a second harmonic generation [30]. To show that our approximation method gives a qualitatively correct result in the last section, we use the finite-element method to demonstrate asymmetric photon localization in a system with similar composition.…”
Section: Introductionmentioning
confidence: 99%
“…In this limitation, we suppose that the energy conversion to the second harmonic is very low such that the fundamental wave remains essentially undepleted. This process is known as a non-depletion approximation in a second harmonic generation [30]. To show that our approximation method gives a qualitatively correct result in the last section, we use the finite-element method to demonstrate asymmetric photon localization in a system with similar composition.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of SSHG can be found in Bloembergen and coworker works [19]. After that, other works are done to study aspects of this phenomenon, such as determining the elements of surface second-order susceptibility tensor [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on surface SHG in semiconductors considered regions on the order of a few nanometers at the material/air interface and demonstrated that this effective volume is a good representation of surface SHG. 28,29,34 Therefore, in our modeling, we consider two regions at the air/GaAs and GaAs/AlGaO interfaces with a thickness of 10 nm each and with a symmetry tensor of pointgroup symmetry mm2. When we include both surface and bulk nonlinearities, with the following surface-induced nonlinear coefficients: χ zxx (2,s) = χ zyy (2,s) = 6χ xzy (2) , χ zzz (2,s) = 6χ xzy (2) , χ yxz (2,s) = χ xzy (2,s) = 1.8χ xzy (2) , while maintaining the surface-induced nonlinear tensor symmetry (see Note S1), we successfully retrieve the twofold symmetry in the total SHG intensity (Figure 3a,c, bottom panels).…”
mentioning
confidence: 99%